Global Burden of Disease of Mercury Used in Artisanal Small-Scale Gold Mining - Nadine Steckling; Myriam Tobollik; Dietrich Plass; Claudia Hornberg; Bret Ericson; Richard Fuller; Stephan Bose-O'Reilly (Annals of Global Health, 2017)
Background: Artisanal small-scale gold mining (ASGM) is the world's largest anthropogenic source of mercury emission. Gold miners are highly exposed to metallic mercury and suffer occupational mercury intoxication. The global disease burden as a result of this exposure is largely unknown because the informal character of ASGM restricts the availability of reliable data. Objective: To estimate the prevalence of occupational mercury intoxication and the disability-adjusted life years (DALYs) attributable to chronic metallic mercury vapor intoxication (CMMVI) among ASGM gold miners globally and in selected countries. Methods: Estimates of the number of artisanal small-scale gold (ASG) miners were extracted from reviews supplemented by a literature search. Prevalence of moderate CMMVI among miners was determined by compiling a dataset of available studies that assessed frequency of intoxication in gold miners using a standardized diagnostic tool and biomonitoring data on mercury in urine. Severe cases of CMMVI were not included because it was assumed that these persons can no longer be employed as miners. Cases in workers' families and communities were not considered. Years lived with disability as a result of CMMVI among ASG miners were quantified by multiplying the number of prevalent cases of CMMVI by the appropriate disability weight. No deaths are expected to result from CMMVI and therefore years of life lost were not calculated. Disease burden was calculated by multiplying the prevalence rate with the number of miners for each country and the disability weight. Sensitivity analyses were performed using different assumptions on the number of miners and the intoxication prevalence rate. Findings: Globally, 14-19 million workers are employed as ASG miners. Based on human biomonitoring data, between 25% and 33% of these miners—3.3-6.5 million miners globally—suffer from moderate CMMVI. The resulting global burden of disease is estimated to range from 1.22 (uncertainty interval [UI] 0.87-1.61) to 2.39 (UI 1.69-3.14) million DALYs. Conclusions: This study presents the first global and country-based estimates of disease burden caused by mercury intoxication in ASGM. Data availability and quality limit the results, and the total disease burden is likely undercounted. Despite these limitations, the data clearly indicate that mercury intoxication in ASG miners is a major, largely neglected global health problem.